Ion beam deposition of diamond-like carbon films - Huck, Hugo Alberto; Jech, Alberto Estanislao; Righini, Raúl; Halac, Emilia Beatriz; Rodríguez de Benyacar, María Angélica; Nicolai, Julio Antonio (1996)
Fil: Huck, Hugo Alberto. Comisión Nacional de Energía Atómica; Argentina.